2019
DOI: 10.26434/chemrxiv.8080043.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cooperative Self-Assembly of Pyridine-2,6-Diimine-Linked Macrocycles into Mechanically Robust Nanotubes

Abstract: <p>Nanotubes assembled from macrocyclic precursors offer a unique combination of low dimensionality, structural rigidity, and distinct interior and exterior microenvironments. Usually the weak stacking energies of macrocycles limit the length or strength of the resultant nanotubes. Imine-linked macrocycles were recently found to assemble into high-aspect ratio (>10<sup>3</sup>), lyotropic nanotubes in the presence of excess acid. Yet these harsh conditions are incompatible with many functi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
103
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(109 citation statements)
references
References 0 publications
6
103
0
Order By: Relevance
“…Unassembled macrocycles do not produce observable diffraction. 32 However, when macrocycles assemble into nanotubes, the emergence of a strong diffraction signal, with a characteristic peak at low values of q related to the macrocycle size (between 0.1 and 0.2 Å -1 ) [31][32][33] is observed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Unassembled macrocycles do not produce observable diffraction. 32 However, when macrocycles assemble into nanotubes, the emergence of a strong diffraction signal, with a characteristic peak at low values of q related to the macrocycle size (between 0.1 and 0.2 Å -1 ) [31][32][33] is observed.…”
Section: Resultsmentioning
confidence: 99%
“…[27][28][29][30] We recently found that the protonation of imine-linked macrocycles triggers strong electrostatic and solvophobic interactions that drive the formation of high-aspect ratio nanotubes. [31][32][33] However, macrocycle assembly that relied exclusively on imine protonation only assembled in the presence of excess acid, whereas lower acid concentrations accelerated macrocycle hydrolysis. [31][32] We subsequently identified a single macrocycle based on pyridine-2,6-dicarboxaldehyde that assembled using sub-stoichiometric quantities of acid, giving rise to robust assemblies that formed fibers with mechanical properties comparable to covalent linear polymers (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to 7% of carbon in trapped, partially mobile furan, 18% of alkene C was detected. Two-dimensional (2D) 13 C- 13 C and 1 H- 13 C NMR identified 12% C in asymmetric O-CH=CH-CH-CH-and 24% in symmetric O-CH-CH=CH-CH-rings. While the former represented defects or chain ends, some of the latter appeared to form repeating thread segments.…”
Section: Introductionmentioning
confidence: 99%